2001
DOI: 10.1155/2001/805379
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in Primary Care: Making Guidelines Work

Abstract: Asthma guideline developers and those interested in enhancing compliance with recommendations will need to attend to factors such as physician attitudes and beliefs on a variety of issues, including the use of objective measures and the availability of adequate resources to conduct the tests. Similarly, negative patient attitudes toward an increased use of corticosteroids suggest that a public education program would be most helpful regarding that group of recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 24 publications
0
25
0
1
Order By: Relevance
“…The reason for these exclusions was the belief that the authors' findings were not consistent with or reflective of the data presented. The remaining 12 studies were published between 1998 and 2006, [25][26][27][28][29][30][31][32][33][34][35][36] and were all published in English (Supplementary Table 2). Five of the studies were from the UK, while the remaining seven were from the US, Canada, and the Netherlands.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reason for these exclusions was the belief that the authors' findings were not consistent with or reflective of the data presented. The remaining 12 studies were published between 1998 and 2006, [25][26][27][28][29][30][31][32][33][34][35][36] and were all published in English (Supplementary Table 2). Five of the studies were from the UK, while the remaining seven were from the US, Canada, and the Netherlands.…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32][33][34][35] Studies indicated that some GPs were sceptical about the evidence…”
Section: Questioning the Guidelinesmentioning
confidence: 99%
See 2 more Smart Citations
“…18,20,21 Lack of engagement with evidence and guidelines suggests a need for an increased primary care research base to inform guideline development.…”
Section: Interpretation Of Findings In Relation To Previously Publishmentioning
confidence: 99%